Recent collection and DNA barcode of the rare Coffee Pot Snowfly Capnia nelsoni (Plecoptera: Capniidae) - Heinold, Brian D. (Illiesia, 2013)
The Coffee Pot Snowfly, Capnia nelsoni Kondratieff & Baumann, was recollected in July 2012 for the first time since the original type material collected in 1981. Scanning electron micrographs of the male and female terminalia are presented and comparisons with similar species are briefly discussed. The first DNA barcode for this species is presented.
Keywords: Capniidae; entomology; Plecoptera; Capnia nelsoni; DNA barcodes; winter stoneflies; Colorado; United States of America; USA